2007
DOI: 10.1128/jcm.00448-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Chromogenic Medium, chromID VRE, for Detection of Vancomycin-Resistant Enterococci in Stool Samples and Rectal Swabs

Abstract: We compared ChromID VRE medium with Enterococcosel containing vancomycin for the detection of vancomycin-resistant Enterococcus in 1,007 specimens. ChromID VRE in combination with Gram straining provided a higher specificity than Enterococcosel, irrespective of the incubation time and enrichment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
22
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
2
22
2
Order By: Relevance
“…Thus, in our experience, stool specimens are inappropriate for direct plating onto the C-ID and CHR media. Our study confirmed that overnight precultivation of stool specimens to enable selective enrichment is essential before specimen plating onto these chromogenic media (2,6).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Thus, in our experience, stool specimens are inappropriate for direct plating onto the C-ID and CHR media. Our study confirmed that overnight precultivation of stool specimens to enable selective enrichment is essential before specimen plating onto these chromogenic media (2,6).…”
supporting
confidence: 70%
“…A cornerstone of those control measures is the detection of noninfected but gut-colonized patients that might serve as a source of the spread of VRE. The use of improved cultural-based methods, e.g., chromogenic media, may provide a feasible alternative for cost-effective VRE surveillance (2,7). This study systematically compared the performance characteristics of chromID VRE (C-ID) medium (bioMérieux, Nürtingen, Germany) with those of CHROMagar VRE (CHR) medium (CHROMagar, Paris, France) with special regard to (i) selectivity, (ii) stability of colony color and growth characteristics, and (iii) the ability to recover VRE from clinical stool specimens.…”
mentioning
confidence: 99%
“…The early detection of VRE may facilitate the timely implementation of infection control measures, and surveillance by examination of fecal and rectal swab specimens has been adopted as a means of reducing outbreaks caused by VRE (16). Recently, it has been reported from Europe and the United States that the use of new chromogenic agars improves the ability to detect VRE isolates from fecal and rectal swab specimens (5,11,12). ChromID VRE agar (cIDVRE; bioMérieux, Marcyl'Etoile, France), which contains 8 mg/liter vancomycin, also has the advantage of differentiating Enterococcus faecalis and Enterococcus faecium, as it detects the ␤-glucosidase and the ␤-galactosidase produced by the two species respectively (5, 11, 12; cIDVRE product insert, reference no.…”
mentioning
confidence: 99%
“…The most common specimens to screen for colonization with VRE are rectal swabs or stool specimens. Several selective and differential media have been developed and evaluated specifically for the purpose of screening for VRE (2)(3)(4)(5)(6)(7)(8)10). Campylobacter (Campy) agar, which supports the growth of VRE and contains 10 g/ml vancomycin, is readily available in most clinical laboratories due to its use in the plating of routine stool cultures to isolate Campylobacter jejuni.…”
mentioning
confidence: 99%